Human interface and the management of information. thematic area, HIMI 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings.: thematic area, HIMI 2019, held as part of the 21st HCI International Conference, HCII 2019, Orlando, FL, USA, July 26-31, 2019, Proceedings. Information in intelligent systems : Part II ([2019]) - Unknown
No abstract available